The adaptation of handwriting recognition system user interface in preschool literacy learning courseware - Saad, Mohd Nizam; Abd Razak, Abd Hadi; Yasin, Azman (2012)
Currently, the education software or simply courseware has successfully become the heart of computer usage in classrooms. With varieties of courseware introduced, the discussion of which courseware assist students the most continues. This paper describes our experience on developing a literacy courseware named handwriting leaning number (HLN) for preschool children.HLN has adapted the handwriting recognition system interface where stylus pen becomes its input modality.By using the stylus pen, we believed that the children could perform better in writing exercise.In order to prove our assumption, we have conducted user satisfaction test using modified questionnaire for user interface satisfaction (QUIS) version 5.5.Result derived from the test indicated that the children tend to satisfy the user interface designed for HLN as the average mean score obtained was 3.864 with Standard Deviation of 0.6879.On the other hand, problems regarding precision and usability of HLN are also reported while solutions to the problems are recommended.